Effective Treatment of Geniospasm: Case Series and Review of the Literature. (17th August 2020) - Hull, Mariam; Parnes, Mered
Background: Geniospasm is a rare genetic disorder characterized by paroxysmal rhythmic or irregular movements of the chin and lower lip due to repetitive contractions of the mentalis muscle. Pathophysiology is poorly understood, and optimal treatment has not been established. Methods: Geniospasm was characterized in a series of patients after evaluation in our clinics, and a comprehensive review of all cases in the medical literature was performed. Results: We evaluated four patients (1 female) in four families with geniospasm, aged 4 months to 9 years. Bothersome symptoms were present in one patient, who was treated with regular injections of onabotulinumtoxinA, with complete resolution of symptoms and no adverse effects. 9 patients in the literature have had similar outcomes. Conclusions: Limited data exist with regard to the effective treatment of geniospasm. Several treatments have been used historically, with variable outcomes. Our results, together with those of prior reported cases, demonstrate benefit of the use of botulinum toxin injections for management of this condition.